2002
DOI: 10.11609/jott.zpj.17.10.919-20
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and utilization of freshwater prawns (Macrobrachium) in river Cauvery in Tamil Nadu

Abstract: River Cauvery, one of the perennial rivers of southern India, originates in Talakaveri, Brahmagiri Hills (12°25'N & 75°34'E) of the Western Ghats, in Coorg District of Karnataka and flows eastwards through Tamil Nadu into Bay of Bengal Sea. It runs a distance of 1171km with many contributories and tributaries. The major reservoir of river Cauvery in Tamil Nadu is Mettur Dam, where from water is usually released for irrigation from July to January. Due to minimum water flow from March to June the river bed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…With this view, the study was conducted to find out length-weight relationship, growth pattern of chelipeds and segments of an endemic freshwater prawn Macrobrachium nobilii (Henderson and Matthai, 1910). Despite its small size, the culture of M. nobilii is encouraged due to its commercial and nutritional value (Mariappan et al, 2002; …”
Section: Introductionmentioning
confidence: 99%
“…With this view, the study was conducted to find out length-weight relationship, growth pattern of chelipeds and segments of an endemic freshwater prawn Macrobrachium nobilii (Henderson and Matthai, 1910). Despite its small size, the culture of M. nobilii is encouraged due to its commercial and nutritional value (Mariappan et al, 2002; …”
Section: Introductionmentioning
confidence: 99%
“…Mariappan et al . () identified the major threat to populations of decapod crustaceans in the River Cauvery as the indiscriminate fishing of female crustaceans, especially during the breeding season. Palaemonid shrimps incubate their eggs attached to the female's abdominal pleopods.…”
Section: Discussionmentioning
confidence: 97%
“…The greatest threat to wild populations of M. rosenbergii in Vembanad Lake is the exploitation of berried females during the peak breeding season which make up 40-60% of the total catch (Jayachandran, 2010). Mariappan et al (2002) identified the major threat to populations of decapod crustaceans in the River Cauvery as the indiscriminate fishing of female crustaceans, especially during the breeding season. Palaemonid shrimps incubate their eggs attached to the female's abdominal pleopods.…”
Section: Threats and Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Freshwater prawns of the genus Macrobrachium Bate, 1868 (Crustacea: Palaemonidae) are a highly diverse group of decapod crustaceans (with 239 species distributed in tropical regions across the world (De Grave et al 2009)) and are often considered as good aquaculture species (New and Singholka 1985;Mariappan et al 2002Mariappan et al , 2003Mariappan and Balasundaram 2004). In particular, Macrobrachium australe Guérin-Méneville 1838, also known as 'chevrette', is a widespread species in the Indo-West Pacific region.…”
Section: Introductionmentioning
confidence: 99%